Bargaining in Collusive Markets - Ola Andersson (Lund University, School of Economics and Management, Department of Economics, 2006)
In this paper we investigate collusion in an infinitely repeated Bertrand duopoly where firms have different discount factors. In order to study how a collusive agreement is reached we model the equilibrium selection as an alternating-offer bargaining game. The selected equilibrium has several appealing features: First, it is efficient in the sense that it entails immediate agreement on the monopoly price. Second, the equilibrium shows how discount factors affect equilibrium market shares. A comparative statics analysis on equilibrium market shares reveals that changes in discount factors may have ambiguous effects on market shares.
Keywords: C72; D43; L11; L41; 330; Bargaining; different discount factors; explicit collusion; market shares